Carbon Dioxide Elimination During Veno-Venous Extracorporeal Membrane Oxygenation Weaning: A Pilot Study. Issue 6 (15th October 2020) - Belliato, Mirko; Cremascoli, Luca; Epis, Francesco; Ferrari, Fiorenza; Quattrone, Maria G.; Malfertheiner, Maximilian V.; Broman, Lars M.; Aliberti, Anna; Taccone, Fabio S.; Iotti, Giorgio A.; Lorusso, Roberto
Abstract : Veno-venous extracorporeal membrane oxygenation (V-V ECMO) represents a component of the treatment strategy for severe respiratory failure. Clinical evidence on the management of the lung during V-V ECMO are limited just as the consensus regarding timing of weaning. The monitoring of the carbon dioxide (CO2 ) removal (V′CO2 TOT) is subdivided into two components: the membrane lung (ML) and the native lung (NL) are both taken into consideration to evaluate the improvement of the function of the lung and to predict the time to wean off ECMO. We enrolled patients with acute respiratory distress syndrome (ARDS). The V′CO2 NL ratio (V′CO2 NL/V′CO2 TOT) value was calculated based on the distribution of CO2 between the NL and the ML. Of 18 patients, 15 were successfully weaned off of V-V ECMO. In this subgroup, we observed a significant increase in the V′CO2 NL ratio comparing the median values of the first and last quartiles (0.32 vs. 0.53, p = 0.0045), without observing any modifications in the ventilation parameters. An increase in the V′CO2 NL ratio, independently from any change in ventilation could, despite the limitations of the study, indicate an improvement in pulmonary function and may be used as a weaning index for ECMO.